La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Publisher: Circuit, musiques contemporaines
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.
Publisher: Circuit, musiques contemporaines

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)
Publisher: University of Nebraska Press

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)
Publisher: University of Illinois Press

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Publisher: Les Presses de l’Université de Montréal
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.
Publisher: Société québécoise de recherche en musique

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

L'âme en tannage de Natasha Kanapé Fontaine : Souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)

Louise Beaudet. De Lotbinière à Broadway - Saint-Pierre, Marjolaine (Éditions du Septentrion, 2017)

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Publisher: Recherches amérindiennes au Québec
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: L'Harmattan

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Publisher: Les Presses de l’Université de Montréal
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
ISBN: 9782913169340 Number: 10 : 1 Publisher: Éditions Mélanie Seteun
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

„A Moncton“ von Marie-Jo Thério. Chiac in Literatur und Alltag [« À Moncton » de Marie-Jo Thério. Le chiac dans la littérature et la vie quotidienne] - Reinsberg, Franziska (Grin Verlag, 2013)
„C'est boring à soir“ - Vielfältiger und vermischter zeigt sich eine Sprache nur selten. Doch was ist das, was dort zu lesen ist? Das Ziel dieser Arbeit ist die Untersuchung der sprachlichen Strukturen dieser besonderen hybriden Sprachvarietät - dem Chiac, eine Varietät des akadischen Französisch, das im Osten Kanadas gesprochen wird.

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.
Publisher: Les Presses de l’Université de Montréal

El cancionero judeoespañol en transición: Un estudio de dos compilaciones de mujeres sefarditas del siglo XX [Le répertoire de chansons judéo-espagnoles en transition : étude de deux compilations de femmes sépharades du XXe siècle] - Havassy, Rivka (Ladinar, 2012)

Quand le rap dit la ville : perceptions sociolinguistiques des rappeuses de Montréal - Lesacher, Claire (Dynamiques sociolangagières de l’espace algérois. Discours et représentations, 2012)

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.
Publisher: Cambridge University Press

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

Récit d’une Beauceronne en Irlande ou la découverte de ‘l’irlandicité’ des Québécois - Matte, Isabelle (Cap-aux-Diamants, 2007)

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

Erika Mann et Pauline Julien : voix parallèles dans l'exil et l'engagement - Augustin, Myriam (Université McGill, 2006)

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian; Québécois; anglophone; francophone; music; newspapers; politics

Questions de renommée : les mises en mémoire du phénomène Céline Dion - Grenier, Line (Recherches féministes, 2000)
Dans cet article, l'auteure se penche sur le « phénomène Céline Dion » au Québec sous l'angle de la renommée. Au moyen de quelques fragments du discours qui a alimenté ce phénomène à la fin de la dernière décennie, l'auteure esquisse les contours de deux des figures concurrentes de la renommée que ce phénomène met en évidence : le « héros national » et l'« entrepreneur heureux ». Son analyse illustre comment ces figures de la renommée et les mises en mémoire auxquelles elles prêtent visibilité et valeur, lorsqu'elles sont en action dans la conjoncture québécoise contemporaine, opèrent une fusion, sinon une collusion entre la réussite individuelle et collective, entre l'intérêt personnel et national, et, par le fait même, rattachent différents ordres de matériel culturel au présent « passé » de certaines expériences privées, ressources locales et trajectoires publiques.
Publisher: Revue Recherches féministes

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Céline Dion et l'identité québécoise. « La petite fille de Charlemagne parmi les grands ! » - Demers, Frederic (VLB Éditeur, 1999)
Pourquoi Céline Dion est-elle une figure identitaire de premier plan aux yeux de la plupart des Québécois? Serait-ce parce qu'elle incarne l'équilibre qu'il recherchent désormais entre la préservation d'un héritage culturel particulier et l'ouverture à l'Autre sous le poids de la mondialisation et du métissage?

Céline Dion, the ADISQ Controversy, and the Anglophone Press in Canada - Young, David (Canadian Journal of Communication, 1999)
Abstract: ADISQ, the organization that honours excellence in the Quebec music industry, gave francophone singer Céline Dion an award for being the Anglophone Artist of the Year in 1990. At the ADISQ gala that year, which was televised live across Canada, Dion refused to accept the award. Dion's decision to not accept the award, and the statement she made when turning it down, became the basis for a controversy that received a great deal of coverage in Canada's anglophone press. This paper examines anglophone press coverage of the ADISQ controversy involving Dion. After outlining press coverage of Dion and ADISQ during the years prior to the controversy, the paper identifies how the controversy began and analyses the issues that dominated the coverage. The paper also examines follow-up coverage of the controversy; it identifies how subsequent news stories on Dion, including some that were written several years later, linked the controversy to other issues. Résumé: L'ADISQ, l'organisme qui reconnaît l'excellence dans l'industrie de la musique au Québec, accorda à la chanteuse francophone Céline Dion le prix du Meilleur Artiste anglophone de l'année 1990. Au gala de l'ADISQ cette année-là-qui fut télévisé en direct partout au Canada-Dion a refusé d'accepter le prix. Cette décision, ainsi que les commentaires que Dion a faites en refusant le prix, suscitèrent une controverse qui fit couler beaucoup d'encre dans la presse anglophone au Canada. Cet article examine comment la presse anglophone a couvert cette controverse de l'ADISQ impliquant Dion. Après avoir tracé les grandes lignes des reportages sur Dion et l'ADISQ dans les années précédant la controverse, cet article identifie comment la controverse commença et analyse les questions qui dominèrent dans la couverture de celle-ci. Cet article examine en outre la couverture suivant la controverse; il identifie comment des reportages ultérieurs sur Dion, y compris certains qui apparurent plusieurs années plus tard, associèrent la controverse à d'autres sujets.
Number: 4
Keywords: ADISQ; Anglophone press; Céline Dion; Journalism

Il fut un temps où l'on se voyait beaucoup, suivi de Lettres africaines et de Tombeau de Suzanne Guité - Julien, Pauline (Lanctôt Éditeur, 1998)

Show Girls - Lam, Meilan (Office national du film du Canada, 1998)
Show Girls celebrates Montreal's swinging Black jazz scene from the 1920s to the 1960s, when the city was wide open. Three women who danced in the legendary Black clubs of the day - Rockhead's Paradise, The Terminal, Café St. Michel - share their unforgettable memories of life at the centre of one of the world's hottest jazz spots. From the Roaring Twenties, through the Second World War and on into the golden era of clubs in the fifties and sixities, Show Girls chronicles the lives of Bernice, Tina and Olga - mixing their memories with rarely seen footage of the era. Their stories are told against a backdrop of the fascinating social and political history that made Montreal a jazz and nightclub hotspot for decades. It is a story of song and dance, music and pride.

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Sierra norteña: The influence of Latin music on the French-Canadian popular song and dance scene, especially as reflected in the career of Alys Robi and the pedagogy of Maurice Lacasse-Morenoff - Sévigny, Jean-Pierre (Productions Juke-box, 1994)

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

Le couple Maubourg-Roberval : un apport décisif à l’implantation de l’art lyrique à Montréal - Paul, Hélène (L'Annuaire théâtral. Revue québécoise d’études théâtrales, 1993)
Un article de la revue L'Annuaire théâtral, diffusée par la plateforme Érudit.

Die Komponistin Violet Archer unter Berücksichtigung ihrer nationalen und internationalen Stellung im Musikleben [La compositrice Violet Archer au regard de sa position nationale et internationale dans la vie musicale] - Glathe, Kerstin (Université de Münster, 1992)

Alanis Obomsawin - Kivi, K. Linda (Canadian Women Making Music, 1992)

Pauline Julien - Kivi, K. Linda (Canadian Women Making Music, 1992)

La question de l'identité dans l'écriture de Pauline Julien - Rheault, Michel (Université du Québec à Montréal, 1991)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Népal. L'échappée belle - Julien, Pauline; Hébert, Denise (VLB Éditeur, 1989)

Éva Gauthier (1885-1958) : première cantatrice canadienne-française d’avant-garde - Turbide, Nadia (Les Cahiers de l'ARMuQ, 1988)

Clémence Desrochers et l'imaginaire social de l'Estrie - Gaulin, André (La chanson en question(s), 1985)

The Rekkukara of the Ainu (Japan) and the Katajjaq of the Inuit (Canada): A Comparison - Nattiez, Jean-Jacques (The World of Music, 1983)

Violet B. Archer : une élève canadienne de Bela Bartok - Lenoir, Yves (Institut supérieur d'archeologie et d'histoire de l'art, Université catholique de Louvain, 1980)

Une Canadienne à Moscou en 1873 - Potvin, Gilles (Bulletin du Centre de recherche en civilisation canadienne-française de l'Université d'Ottawa, 1979)

Entre cri et chant. Les katajjait, un genre musical féminin - Saladin d'Anglure, Bernard (Études/Inuit/Studies, 1978)
The growing popularity in the West of various graphic or plastic expressions of contemporary (or prehistoric) Inuit art has overshadowed other aspects of Inuit art — particularly traditional music, within which throat games represent a most fascinating genre. Indeed, some of the first western travelers who attended a katajjaq performance were to pay a high price to have their curiosity satisfied — as we shall see in the following documents. The anthropologist cannot escape this fascination either, for the katajjait constitute a complex and ambiguous genre, belonging to cry and language, song and dance, game and music, ritual and performance, expressing Inuit symbolism on the relationship between man and woman, the relationship to nature and the supernatural and reflecting elements of the social structure since the performance of katajjait requires cooperation and sometimes gives rise to competition between performers. Le succès croissant en occident des différentes expressions graphiques ou plastiques de l'art inuit contemporain (ou préhistorique) a masqué d'autres aspects de l'art inuit, en particulier l'art musical traditionnel au sein duquel les jeux de gorge (notamment les katajjait) constituent un genre fascinant. Plusieurs des premiers voyageurs occidentaux qui y assistèrent en firent l'expérience à leurs dépens comme nous le verrons dans les documents qui suivent. Genre fascinant aussi pour l'anthropologue en raison de sa complexité et de son ambiguïté qui le font relever à la fois du cri et du langage, du chant et de la danse, du jeu et de la musique, du rite et de la performance; en raison également et de sa dimension symbolique lorsqu'il traite du rapport à la nature, du rapport au surnaturel et du rapport homme-femme, et de sa dimension sociologique à travers la coopération nécessitée par son exécution et la compétition parfois organisée entre les exécutants.

Recherches en ethnomusicologie: les katajjait chez les Inuit du Nouveau-Québec - Montpetit, Carmen; Veillet, Céline (Études/Inuit/Studies, 1977)

Mémoires d’Emma Albani. L’éblouissante carrière de la plus grande cantatrice québécoise - Albani, Emma (Éditions du Jour, 1972)